Originally Posted by
jessaray I need to figure out this function before I can do the actual problem that concerns the function. I don't know why I'm having so much trouble with this, but I just can't figure it out!
S(0) = 1, S(1) = 0, and S(n+1) = 3S(n) – 2S(n-1)
Express S(n) as a function of n.
And the letters/numbers in parenthesis are supposed to be subscripts of each S.
These are the first 6 numbers in the sequence.
S(0) = 1
S(1) = 0
S(2) = -2
S(3) = -6
S(4) = -14
S(5) = -30
S(6) = -62
Any help?